DESIGN AND IMPLEMENTATION OF FLOATING – POINT MULTIPLIER USING IEEE -754 STANDARD - SHAFIA TASNEEM (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
DESIGN AND IMPLEMENTATION OF FLOATING – POINT MULTIPLIER USING IEEE -754 STANDARD